INTEGRATING QUALITATIVE INQUIRY AND SURVEY RESEARCH IN SOCIAL SCIENCES: A DESCRIPTIVE AND ANALYTICAL LITERATURE REVIEW - Abd Fatah, Rahmat (International Journal of Multidisciplinary Reseach, 2025)
Recent developments in contemporary social sciences indicate a growing need for methodological approaches capable of explaining the complexity of social reality in a manner that is both in-depth and representative. The longstanding tension between the depth of meaning offered by qualitative research and the breadth of generalization associated with survey research has driven the advancement of mixed methods as an integrative research strategy. This article aims to map and analyze global trends in the integration of qualitative and survey methods in social science research through a descriptive and analytical literature review approach. The literature search was conducted using reputable international databases, namely Scopus and Web of Science, supplemented by Google Scholar, covering publications from 2000 to 2024. The selected articles consist of peer-reviewed publications that explicitly discuss or apply the integration of qualitative and survey approaches. The analysis employs thematic and conceptual synthesis to identify epistemological rationales, dominant methodological design patterns, the strategic role of surveys, and levels of methodological integration in social research practice. The findings indicate that pragmatism constitutes the dominant epistemological foundation, accompanied by hybrid practices that combine interpretivist and post-positivist logics. Sequential designs, particularly the sequential exploratory design, emerge as the most globally prevalent pattern, while surveys play a strategic role not only as instruments of quantification but also as mechanisms for generalizing qualitative findings, validating constructs, and constructing social typologies. The findings further reveal that methodological integration most frequently occurs at the design and interpretation stages, whereas integration at the analytical stage remains limited. This article contributes to methodological reflection by emphasizing the importance of coherence in integration logic as a fundamental prerequisite for meaningful and scientifically accountable mixed methods practice in social science research.